Combined effects of light and salinity on the growth performance in juveniles of the Malabar grouper, Epinephelus malabaricus - Yafan Zhu; Kodai Fukunaga; Shingo Udagawa; Siqi Lu; Akimichi Shimabukuro; Akihiro Takemura (Frontiers in Marine Science)
IntroductionEnvironmental factors, including light and salinity, influence fish growth. It has been hypothesized that optimizing environmental factors can activate the endocrine system and enhance the growth performance of fish. The aim of the present study was to understand how environmental factors affect the growth performance of juveniles of the Malabar grouper, Epinephelus malabaricus, a valuable species in Asian markets. The combined effects of light wavelength and salinity on growth performance were closely evaluated because each of them had a positive effect on growth stimulation in this species.MethodsJuvenile Malabar groupers were reared under combined conditions of blue LED light (BL, 463 nm) and red LED light (RL, 623 nm) at low salinity (LS, 11psu) and high salinity (HS, 34 psu) for two weeks. Biometric parameters were quantified, and related gene expressions were analyzed via qPCR.ResultsSpecific growth rate (SGR) was significantly higher in fish under BL/LS, followed by RL/LS and BL/HS. A higher condition factor (CF) was observed in fish under BL/LS, whereas a lower food conversion rate (FCR) was observed in fish under BL/LS and RL/LS. The transcript levels of acetyl-CoA carboxylase (acaca) and fatty acid synthase (fas) in the liver increased under BL/LS (vs. RL/LS). BL upregulated neuropeptide Y (npy), but not pro-opiomelanocortin (pomc), in the fish brain under both salinities. Transcript levels of growth hormone (gh) in the pituitary gland and insulin-like growth factor-1 (igf-1) in the liver were significantly lower in fish under BL/LS than in those under BL/HS. DiscussionThe promotion of growth performance in juvenile Malabar groupers were attributable to the additive effects of light wavelength and salinity. Since we demonstrated the combined effects of blue light and isosmotic salinity on lipogenesis and somatic growth, optimization of light and salinity conditions can enhance the aquaculture productivity of Malabar groupers.